PERSUASIVE LANGUAGE IN ADVERTISING FASHION PRODUCTS OF FASHION E-COMMERCE COURSE AT UNIVERSITAS NEGERI PADANG - Nurul Inayah Hutasuhut; Siti Isma Sari; Samuel Martin Pradana (Ensiklopedia of Journal, 2023)
This research was conducted to analyze the persuasive language used by fashion design students Universitas Negeri Padang for fashion products advertisement in e-commerce fashion courses. Fashion students promote their products on e-commerce websites, such as Facebook, Instagram, Shopee and other e-commerce applications or websites. Researchers want to know the persuasive language used in the ad because there is no previous research. To be a reference for local entrepreneurs in using persuasive language in advertisements for fashion businesses. And become a reference for learning material for fashion students in fashion e-commerce courses. This research uses qualitative methods. This method was chosen by the researcher because this research uses text as data and includes several processes in data analysis. This information was obtained from several fashion business e-commerce websites used by Universitas Negeri Padang fashion design students to promote their products in fashion e-commerce course. The researchers used posting and descriptions, which are statements and phrases, to assess the research data. The researcher's initial step in analyzing the data is to classify it according to the theory of persuasive language. The next step was to interpret the message contained in the ad. And the last step was to conclude the research. The sample group included 100 descriptions and slogans from students' e-commerce addresses. Alliteration was found to be the most often employed literary device, followed by imagery and assonance. The persuasive  was mostly used in advertising captions to describe product attributes, illustrate the items, actions or feelings, and emphasize.